An anomalous addition of chlorosulfonyl isocyanate to a carbonyl group: the synthesis of ((3aS,7aR,E)-2-ethyl-3-oxo-2,3,3a,4,7,7a-hexahydro-1H-isoindol-1-ylidene)sulfamoyl chloride - Köse, Aytekin; Ünal, Aslı; Şahin, Ertan; Bozkaya, Uğur; Kara, Yunus (Beilstein Journal of Organic Chemistry, 2019)
In this study, we developed a new addition reaction of chlorosulfonyl isocyanate (CSI), starting from 2-ethyl-3a,4,7,7a-tetrahydro-1H-isoindole-1,3(2H)-dione. The addition reaction of CSI with 2-ethyl-3a,4,7,7a-tetrahydro-1H-isoindole-1,3(2H)-dione resulted in the formation of ylidenesulfamoyl chloride, whose exact configuration was determined by X-ray crystal analysis. We explain the mechanism of product formation supported by theoretical calculations.
Keywords: addition reaction; chlorosulfonyl isocyanate; sulfamoyl chloride; theoretical calculations

(untitled) - Graf, R. (Chem. Ber., 1959)

(untitled) - Clauβ, K. (Justus Liebigs Ann. Chem., 1969)

(untitled) - Graf, R. (Angew. Chem., Int. Ed. Engl., 1968)

(untitled) - Moriconi, E. J.; Jalandoni, C. C. (J. Org. Chem., 1970)

(untitled) - Vorbrüggen, H. (Tetrahedron Lett., 1968)

(untitled) - Hoffmann, R.; Woodward, R. B. (J. Am. Chem. Soc., 1965)

(untitled) - Woodward, R. B.; Hoffmann, R. (Angew. Chem., Int. Ed. Engl., 1969)

(untitled) - Moriconi, E. J.; Kelly, J. F. (Tetrahedron Lett., 1968)

(untitled) - Bestian, H.; Biener, H.; Clauss, K.; Heyn, H. (Justus Liebigs Ann. Chem., 1968)

(untitled) - Paquette, L. A.; Wyvratt, M. J.; Allen, G. R., Jr (J. Am. Chem. Soc., 1970)

(untitled) - Moriconi, E. J.; Crawford, W. C. (J. Org. Chem., 1968)

(untitled) - Van Allan, J. A.; Chang, S. C.; Reynolds, G. A. (J. Heterocycl. Chem., 1974)

(untitled) - Rao, K. R.; Nageswar, Y. V. D.; Srinivasan, T. N.; Sattur, P. B. (Synth. Commun., 1988)

(untitled) - Castellanos, L.; Duque, C.; Zea, S.; Espada, A.; Rodríguez, J.; Jiménez, C. (Org. Lett., 2006)

(untitled) - Bartsch, H.; Schwarz, O. (Arch. Pharm. (Weinheim, Ger.), 1982)

(untitled) - Tan, A.; Koc, B.; Şahin, E.; Kishali, N. H.; Kara, Y. (Synthesis, 2011)

(untitled) - Tan, A.; Kazancıoğlu, M. Z.; Aktaş, D.; Gündoğdu, Ö.; Şahin, E.; Kishali, N. H.; Kara, Y. (Turk. J. Chem., 2014)

SHELXS-97, SHELXL-97 Program for Crystal Structure Solution and Refinement (University of Göttingen, 1997)

(untitled) - Becke, A. D. (J. Chem. Phys., 1993)

(untitled) - Lee, C.; Yang, W.; Parr, R. G. (Phys. Rev. B, 1988)

(untitled) - Vosko, S. H.; Wilk, L.; Nusair, M. (Can. J. Phys., 1980)

(untitled) - Stephens, P. J.; Devlin, F. J.; Chabalowski, C. F.; Frisch, M. J. (J. Phys. Chem., 1994)

(untitled) - Hariharan, P. C.; Pople, J. A. (Theor. Chim. Acta, 1973)

(untitled) - McLean, A. D.; Chandler, G. S. (J. Chem. Phys., 1980)

(untitled) - Krishnan, R.; Binkley, J. S.; Seeger, R.; Pople, J. A. (J. Chem. Phys., 1980)

Gaussian 09, Revision D.01 (Gaussian, Inc., 2013)